2014
DOI: 10.3109/07420528.2014.925469
|View full text |Cite
|
Sign up to set email alerts
|

Daily rhythms are retained both in spontaneously developed sarcomas and in xenografts grown in immunocompromised SCID mice

Abstract: The circadian clock generates and regulates many daily physiological, metabolic and behavioral rhythms as well as acute responses to various types of stresses including those induced by anticancer treatment. It has been proposed that modulatory function of the clock may be used for improving the therapeutic efficacy of established anti-cancer treatments. In order to rationally exploit this mechanism, more information is needed to fully characterize the functional status of the molecular clock in tumors of diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…Currently, there are few studies on the circadian clock of cancers. The findings have ranged from cancer tissue being arrhythmic, to being rhythmic but out of phase with normal tissue, to being rhythmic and in phase with normal tissue (18,19,(39)(40)(41)(42)(43)(44). It is necessary to determine the circadian phase and amplitude relationships between cancer and normal tissues to develop truly mechanism-based chronotherapy regimens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there are few studies on the circadian clock of cancers. The findings have ranged from cancer tissue being arrhythmic, to being rhythmic but out of phase with normal tissue, to being rhythmic and in phase with normal tissue (18,19,(39)(40)(41)(42)(43)(44). It is necessary to determine the circadian phase and amplitude relationships between cancer and normal tissues to develop truly mechanism-based chronotherapy regimens.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the TS and NTS of diurnally expressed genes are repaired out of phase. As it has been reported that cancers may have circadian rhythms in phase with the host (18) or out of phase with…”
mentioning
confidence: 99%
“…Not all studies, however, have shown suppressed circadian clock gene oscillations in cancer cells/tumour tissue. Comas et al found that fibrosarcoma cells and mouse sarcomas in vivo display significant rhythmic profiles of PER2 ‐ and BMAL1 ‐driven luciferase expression, similar to that found in normal tissues, although with slightly reduced amplitude . Moreover, U2OS osteosarcoma cells are often used as a cell line in which to study circadian rhythms due to the robust circadian oscillations observed in these cells .…”
Section: Circadian Rhythm Disruption In Cancermentioning
confidence: 97%
“…Concerning circadian rhythms in oncological diseases, plentiful opposing, and tissue specific results can be found. Some studies report that tumors do indeed show rhythmic circadian gene expression [128], while others indicate that cancerous tissue either lacks rhythmicity or expression of clock genes is compromised [129,130]. Recent studies have declared absence of circadian rhythm in TGCTs, although some authors proposed that cyclic expression of clock genes in testes is suspended due to cellular differentiation during spermatogenesis [126,131].…”
Section: Chronobiologymentioning
confidence: 99%